LUCRETIUS 5.1442 PROPTER ODORES: THE SWEET SMELL OF (VERY BELATED) SUCCESS?. (9th June 2015) - Mitchell, Keith
Abstract : This paper offers a new reading of the end of Lucretius 5.1442, arguing that the line-end as we have it (much less Servius' apparent reference to it) cannot stand, but that the original reading may yet be recovered from the transmitted text. The paper also seeks to show how the corruption may have arisen.